Watermelon‐Derived Extracellular Vesicles Influence Human Ex Vivo Placental Cell Behavior by Altering Intestinal Secretions. Issue 19 (19th August 2022) - Timms, Kate; Holder, Beth; Day, Anil; Mclaughlin, John; Forbes, Karen A.; Westwood, Melissa
Abstract : Scope: During pregnancy, mother‐to‐fetus transfer of nutrients is mediated by the placenta; sub‐optimal placental development and/or function results in fetal growth restriction (FGR), and the attendant risk of stillbirth, neurodevelopmental delay, and non‐communicable diseases in adulthood. A maternal diet high in fruit and vegetables lowers the risk of FGR but the association cannot be explained fully by known macro‐ and micronutrients. Methods and results: This study investigates if dietary‐derived extracellular vesicles (EVs) can regulate placental function. The study characterizes the microRNA and protein cargo of EVs isolated from watermelon, show they are actively internalized by human intestinal epithelial cells in vitro, use mass spectrometry to demonstrate that they alter the intestinal secretome and bioinformatic analyses to predict the likely affected pathways in cells/tissues distal to gut. Application of the watermelon EV‐modified intestinal secretome to human placental trophoblast cells and ex vivo tissue explants affects the trophoblast proteome and key aspects of trophoblast behavior, including migration and syncytialization. Conclusion: Dietary‐derived plant EVs can modify intestinal communication with distal tissues, including the placenta. Harnessing the beneficial properties of dietary‐derived plant EVs and/or exploiting their potential as natural delivery agents may provide new ways to improve placental function and reduce rates of FGR. Abstract : (A) The content of watermelon extracellular vesicles (EVs) differs from watermelon cells. (B) Plant EVs are known to survive digestion; here we show (C) they are internalised into intestinal epithelial cells in vitro, (D) resulting in an altered basal secretome (representing post‐digestion circulation), and beneficial changes to placental function in vitro: increased (E) syncytialisation and (F) migration of extravillous trophoblasts.